Containing medical expenditure: lessons from reform of Beijing public hospitals. (22nd June 2019) - Liu, Xiaoyun; Xu, Jin; Yuan, Beibei; Ma, Xiaochen; Fang, Hai; Meng, Qingyue
Abstract : Beijing's reforms have succeeded in reducing hospitals' reliance on drug sales and shifting patients to primary care, say Xiaoyun Liu and colleagues